Natural and anthropogenic impact on the formation of archaeological layers in a lake shore area: case study from the Serteya II site, Western Russia - Mazurkevich, Andrey; Kittel, Piotr; Maigrot, Yolaine; Dolbunova, Ekaterina; Mroczkowska, Agnieszka; Wieckowska-Lüth, Magda; Piech, Wiktor (Acta Geographica Lodziensia, 2020)
The article presents the results of a study on archaeological structures and horizons developed in the palaeolake shore-zone of the Serteya II site that was occupied intermittently and to a greater or lesser intensity from the Mesolithic up to the Middle Ages. The Serteya II site is a multilayer complex used by hunter–fisher–gatherer communities in the 9th–8th mill. BC, and from the end of the 7th till the end of the 3rd mill. BC. The article is focused on the particularities of the formation of archaeological layers and the reconstruction of the ancient environment in different periods of time. The study of the sets of artefacts, their state of preservation, as well as the traits of archaeological features, may indicate the peculiarities of the formation of different sedimentological units. Based on the results of complex natural-scientific research it was possible to reconstruct the palaeo-ecology of changing water regimes as well as changes in environmental conditions.